Evaluation of Antibacterial Activity of Hinguleshwar Rasa (AYUSHDHARA, 2023)
In this era infectious diseases are posing problems for human beings. In order to avoid various infections, production and use of antibiotics is on rise. The widespread misuse of antimicrobials is responsible for emerging microbial resistance. Numbers of Ayurvedic classical preparations were being used in cases of infections, and they were found to be effective clinically. Therefore, to make our treatment scientifically more validated, we can assess the antimicrobial activity of such preparations in vitro (i.e., culture and sensitivity tests). The development of bacterial resistance to known antibiotics and adverse effect to presently available antibiotics has necessitated the search for new antibacterial agents in different systems of medicine. So Hinguleshwar rasa, a known traditional medicine, has been selected for this study. The antibacterial activity of the Hinguleshwar rasa was tested against pathogenic bacteria strain Streptococcus pyogenes, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Salmonella typhi. In order to study antibacterial action of Hinguleshwar rasa in vitro well diffusion method. During this study Hinguleshwar rasa was trailed with bacteria at different concentrations. To correlate the result, control solutions were prepared by streptomycin. Experimental groups were compared with control groups and observations were noted.